The performance of asphalt binder with trichloroethylene: Improving the efficiency of using reclaimed asphalt pavement. (20th September 2019) - Ge, Dongdong; You, Zhanping; Chen, Siyu; Liu, Chaochao; Gao, Junfeng; Lv, Songtao
Abstract: The objectives of this research are to investigate the effect of solvent in asphalt binder, and to propose a method to determine the actual performance of asphalt binder extracted from asphalt mixture thus improving the efficiency of using RAP. The Fourier-transform infrared spectroscopy (FTIR) test was used to analyze the functional groups of trichloroethylene (TCE) and asphalt binder with TCE. This test also qualitatively and quantitatively evaluated the influence of solvent in asphalt binder. Dynamic Shear Rheometer (DSR) test was employed to measure the complex shear modulus (|G ∗ |) of asphalt binder with different TCE contents and to establish the relationship between the TCE contents and the |G ∗ | of asphalt binder. Based on the testing results, functional group = C–H of TCE can be used as an indicator to verify the existence of TCE in the extracted asphalt binder. Both band areas 834-848 cm -1 and 918-938 cm -1 changed for PG 58–28 and Pressure Aging Vessel (PAV) aged PG 58-28 binder after the addition of TCE. Band area 918-938 cm -1 can better reflect the influence of TCE in asphalt binder. Band area 834-848 cm -1 did not change when TCE content was at a low level. Both the existence of TCE and the content of TCE had a significant influence on the |G*| of unaged and PAV aged PG 58–28 asphalt binder. A regression function was built to establish the relationship between the TCE content and |G*|. With the method developed in this study, the correlation between the TCE amount and the FTIR spectrum area was quantified. The actual |G ∗ | of asphalt binder without TCE can be back calculated. The method used in this study provided guidance for the determination of asphalt binder performance extracted from RAP, which can be beneficial to the design of asphalt mixtures with RAP.